Filmes e revestimentos comestíveis a base do polissacarídeo sulfatado da alga vermelha (Hypnea musciformis) incorporados de ácido cafeico para aplicação em pescado - Matos, Jaqueline Alves de (2020)
There are several materials forming edible films and coatings. In this context, red macroalgae are noted for being rich in sulfated polysaccharides (PS) such as carrageenan, which has good mechanical and barrier properties. The present study aimed to produce edible films based on carrageenan, with different concentrations of plasticizer (glycerol), and the incorporation of caffeic acid. Carrageenan was extracted from red algae (Hypnea musciformis) and characterized physically-chemically, through the analysis of: chemical composition, DSC, TGA, FTIR, 1H NMR and 13C and gel electrophoresis. The physical, mechanical and antimicrobial properties of the film-forming solution (glycerol + caffeic acid) were determined to evaluate the efficiency of this coating aiming at possible applications in fish products. The red algae showed a yield of approximately 28.4 % of the carrageenan per weight of dry algae, in addition no protein contaminants were detected. The values obtained for the centesimal composition referring to moisture, ash, lipids and PS proteins were 20.9 %, 21.28 %, 0.69 % and 14.37 %, respectively. Thermal evaluation (DSC and TGA) showed that the PS is thermostable and can be used in the formation of edible films. FTIR analysis identified the presence of functional groups characteristic of agarocolloids. Agarose gel electrophoresis revealed that the PS has a polydispersed band along the gel with a heterogeneous characteristic. No other substituents were identified by 1H NMR and 13C analysis, with only the presence of sulfate in the polysaccharide. The edible films produced in this work showed flexibility, homogeneity and solubility in water. Visibly, these films exhibited a yellowish green color and low opacity. The incorporation of glycerol in the films promoted an increase in water vapor permeability. Low stress and strain values at break suggest the use of a not purified polysaccharide. An antimicrobial activity was verified in the 2.0% PS filmogenic solution, presenting an inhibition halo for Gram-negative and Gram-positive bacteria. For coffee acid, this activity was positive for Gram-negative bacteria (Vibrio parahaemolyticus) and Gram-positive bacteria (Staphylococcus aureus). As it is produced in the consumer and biodegradable in the environment, editable films are allowed in the present work, potentially having potential for application in fish.